Consensus-Expressed CXCL8 and MMP9 Identified by Meta-Analyzed Perineural Invasion Gene Signature in Gastric Cancer Microarray Data - Jia, Xiuzhi; Lu, Minjia; Rui, Chen; Xiao, Ying (Frontiers in Genetics, 2019)
As an under-recognized route of cancer metastasis, perineural invasion (PNI) can be defined as the procedure of neoplastic invasion of nerves, which can be targeted to inhibit the metastasis of malignant cancer. However, the underline mechanism of PNI in cancer is still unknown. We constructed a PNI gene signature based on Pathway Studio mediated literature screen and sought to investigate these genes in a gastric cancer model. Thus, a total of 467 studies/datasets were retrieved in Gene Expression Omnibus database (GEO) using the keywords “gastric cancer”, among which 13 studies focused on gene expression profiling were further manually inspected and selected. Furthermore, the constructed PNI gene signature (104 genes) expression was meta-analyzed, and consensus expressed C-X-C Motif Chemokine Ligand 8 (CXCL8) and matrix Metallopeptidase 9 (MMP9) (p<0.01, |LFC|>1) were detected. Importantly, the disease-free survival was significantly worse in patients with high expression of CXCL8 and MMP9 than that in patients with low expression of CXCL8 and MMP9 (P = 0.05). Moreover, the multiple linear regression (MLR) analysis showed that the population region (country) was associated with the expression of both CXCL8 and MMP9. In conclusion, these data suggested that the co-expressed CXCL8 and MMP9 could be early detection marker for PNI, with a potential to be utilized as individual or racial therapy target for early treatment to prevent PNI related cancer metastasis.